Real-world business intelligence with Microsoft Dynamics GP : become an expert at preparing reports using Dynamics GP quickly and efficiently /: become an expert at preparing reports using Dynamics GP quickly and efficiently. (2015) - Allen, Belinda; Polino, Mark
No abstract available